Fluidelastic Instability of Tube Arrays Subjected to Axisymmetric Jet Flow - Ledger, Buddy (My University, 2015)
An experimental scale model study was conducted to investigate the onset of fluidelastic instability in a tube array subjected to axisymmetric jet flow. A tube array was constructed using aluminum tubes with 44.45 mm outer diameter, $D$, which were arranged in a square pattern with 88 mm pitch, $P$. The pitch to diameter ratio, $P/D$, was approximately 2.0. The tubes were flexibly mounted using threaded rod and tuned to a first mode natural frequency, $f_n$, of 9 Hz. Auxiliary damping devices were added to each tube, and tuned, to achieve a damping ratio, $\zeta$, of 1 % of critical. The mass damping parameter, $m(2 \pi \zeta)/(\rho D^{2})$, of the tube array was 27.9. The tube array was tested under uniform flow conditions in McMaster University's 2 ft wind tunnel to establish the critical reduced velocity, $V_{cr}/(f_n D)$, of 30.0 at the onset of fluidelastic instability. The uniform flow test established a basis for comparing the results with the existing literature and evaluating the validity of the proposed partial admission calculation. The tube array was also tested in open air using an axisymmetric jet, with two different physical arrangements, the first with the jet aimed between tubes and perpendicular to the tube spans and the second with the jet aimed at a tube face and perpendicular to the tube spans. In each case the jet flow velocity was incrementally increased to characterize the onset of fluidelastic instability. To characterize the flow dispersion through the tube array a series of velocity profile measurements were also collected. The measured velocity profiles were used to estimate the spanwise function of transverse average gap velocity, $\bar{V}(x)$, which was used to predict the equivalent critical uniform gap flow velocity, $V_{cr}$, using the concept of partial admission. The predicted $V_{cr}$ values showed reasonable agreement with the experimental results. However, the prediction method did indicate instabilities in tube rows where instability was not actually observed. A simplified prediction approach was developed which was based on using a predicted three dimensional velocity profile, $V(x,y)$, at the $z$ location of the first row tube gap, under the assumption of free field conditions, to calculate an estimate of the spanwise function of transverse average gap velocity, $\bar{V}(x)$. Although the predictions of $V_{cr}$ agreed reasonably well with the experimental results, first row instabilities were not observed in any of axisymmetric jet flow experiments. Therefore, this method can be used to estimate the the critical uniform gap velocity, $V_{cr}$, but not the spatial location of the instability. Based on the results of the experiments and calculations, adoption of the modified partial admission formula is recommended and possible avenues for further investigation and verification are suggested.
Keywords: Fluidelastic Instability; Partial Admission; Submerged Axisymmetric Turbulent Jet; Equivalent Velocity